Effects of transcutaneous electric nerve stimulation on pain after episiotomy. A systematic review and meta-analysis - Elisa López-Campos; Mercedes Soto-González; Alejandra Alonso-Calvete; Iria Da Cuña-Carrera (Heliyon)
Background: Episiotomy is a surgical intervention performed during the second stage of labor to facilitate the baby's exit through the birth canal. There are different reasons that lead to an episiotomy; however, it is recommended to be performed occasionally and not systematically, since it may produce negative effects such as pain. Different therapies have been described to reduce this pain, including transcutaneous electrical nerve stimulation (TENS). Objective: To conduct a systematic review and meta-analysis about the effects of Transcutaneous Electric Nerve Stimulation (TENS) on pain after episiotomy. Methods: The databases PubMed, Cochrane, Scopus, Cinhal, PEDro and Web of Science were consulted using the terms “Episiotomy” and “Transcutaneous Electric Nerve Stimulation”. The methodological quality was analyzed with the PEDro scale. A random-effects model was used to carry out the meta-analysis. Findings: 88 studies were obtained and after applying the selection criteria, 6 were included in the systematic review and 5 in the meta-analysis. There were significant positive effects in decreasing the pain for TENS in comparison with pre-intervention (SMD = 1.19 [95 % CI – 0.33 to 2.05]; p < 0.01; I2 = 96 %), control group (SMD = −1.07 [95 % CI – −1.53 to −0.6]; p < 0.01; I2 = 82 %) and placebo group (SMD = −1.33 [95 % CI – −2.32 to −0.34]; p < 0.01; I2 = 86 %). Conclusion: TENS appears to have a positive effect in reducing pain after 1 h of an episiotomy. The location of the electrodes does not seem to be relevant in the effects.